Advances in Nanocomposite-Based Fertilizers for Sustainable Agricultural Practices - Nadeem Ullah; Amjid Khan; Tahira Younis; Haris Maqbool; Mehwish Iqbal; Muhammad Ali; Zabta Khan Shinwari (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2025)
Nanotechnology is having a significant impact in the field of agriculture, providing solutions to increase agricultural output to solve environmental issues. It promotes sustainable agriculture and successfully solves the current crisis of global food security. Sustainable agriculture is vital for securing food deliveries, maintaining resources, and combating environmental impact. The objective of this review is the recent development of nanocomposites based fertilizers in promoting agricultural sustainability. The use of traditional agricultural fertilizers indicates high nutrient losses of 80-90% of phosphorus and 50-70% of nitrogen contributing to environmental pollution. To cope with these demands, advancement in nanotechnology, such as nanocomposites-based fertilizers, is a substitute. Prominent trials in field scale indicate that zinc oxide nanocomposites enhanced crop yields by 25-30% though reducing fertilizer application rates up to 50%. Chitosan based nanocomposites demonstrated dual benefits of improved nutrient uptake and disease resistance, increasing plant biomass by 15-20%. The Nanocomposites based fertilizers are ecologically friendly, reduce environmental issues, provide sustainability to agriculture and agronomy, promote crop productivity, reduce the wastage of traditional fertilizers, and improve soil health. This review is estimated to cheapen and transform agricultural practices, increasing sustainability and productivity for shareholders and all associates for upcoming generations.